PENGARUH PERBANDINGAN TEPUNG JANTUNG PISANG, TEPUNG KACANG HIJAU, DENGAN TEPUNG TERIGU DAN PENAMBAHAN GUM ARAB TERHADAP MUTU COOKIES JANTUNG PISANG (The Effect of Ratio Inflorescence of Banana Flour, Mung Bean Flour, With Wheat Flour and Addition of A - Refianti Siahaan; Ismed Suhaidi; Rona J. Nainggolan (Jurnal Rekayasa Pangan dan Pertanian, 2018)
ABSTRACT The purpose of this study was to determine the effect of ratio  inflorescence of banana flour, mung bean flour, wheat flour, and addition of arabic gum on the quality of cookies. The research was designed using  completely randomized design with two factors, i.e ratio of inflorescence of banana flour, mung bean flour, with wheat flour (T) : (10%: 40%: 50%, 20%: 30%: 50%, 30%: 20%: 50%, and 40%: 10%: 50%) and the addition of arabic gum (P): (0.5%, 1.0%, 1.5%, and 2.0%).    The of ratio inflorescence of banana flour, mung bean flour, and wheat flour had highly significant effect on the moisture, ash, protein, fat, carbohydrate, fiber contents along with organoleptic hedonic of color, flavour, taste, texture values and organoleptic score of color, texture, and general acceptance values. Moreover, the addition of arabic gum had highly significant effect on the protein and fiber contents, organoleptic hedonic flavour and texture values, and also organoleptic score of texture. Furthermore , the interaction of the two factors had significant effect on the fiber content, organoleptic hedonic and score of texture values. The ratio of inflorescence of banana flour, mung bean flour, with wheat flour 10%: 40%: 50%, respectively  (T1) and the addition of arabic gum 0.5% (P1) produced the best cookies. Keywords: Arab Gum, Cookies, Inflorescence of Banana  Flour, Mung Bean Flour   ABSTRAK Penelitian ini dilakukan untuk mengetahui pengaruh perbandingan tepung jantung pisang, tepung kacang hijau, dengan tepung terigu dan penambahan gum arab terhadap mutu cookies jantung pisang. Penelitian ini menggunakan rancangan acak lengkap dengan dua faktor, yakni perbandingan tepung jantung pisang, tepung kacang hijau, dengan tepung terigu (T) : (10%:40%:50%, 20%:30%:50%, 30%:20%:50%, dan 40%:10%:50%) dan penambahan gum arab (P) : (0,5%, 1,0%, 1,5%, dan 2,0%). Perbandingan tepung jantung pisang, tepung kacang hijau, dengan tepung terigu memberi pengaruh berbeda sangat nyata terhadap kadar air, kadar abu, kadar protein, kadar lemak, kadar karbohidrat, kadar serat, nilai hedonik warna, nilai hedonik aroma, nilai hedonik rasa, nilai hedonik tekstur, nilai skor warna, nilai skor tekstur, dan penerimaan umum. Penambahan gum arab memberi pengaruh berbeda sangat nyata terhadap kadar protein, kadar serat, nilai hedonik aroma, nilai hedonik tekstur,  dan nilai skor tekstur. Interaksi kedua faktor memberi pengaruh berbeda nyata terhadap kadar serat, nilai hedonik tekstur, dan nilai skor tekstur. Perbandingan tepung jantung pisang, tepung kacang hijau, dengan tepung terigu 10:40:50% (T1) dan penambahan gum arab 0,5% (P1) menghasilkan cookies dengan mutu terbaik.   Kata kunci : Cookies, Gum Arab, Tepung Jantung Pisang, Tepung Kacang Hijau